Single CuO nanowires decorated with size-selected Pd nanoparticles for CO sensing in humid atmosphere. (9th April 2015) - Steinhauer, Stephan; Singh, Vidyadhar; Cassidy, Cathal; Gspan, Christian; Grogger, Werner; Sowwan, Mukhles; Köck, Anton
Abstract: We report on conductometric gas sensors based on single CuO nanowires and compare the carbon monoxide (CO) sensing properties of pristine as well as Pd nanoparticle decorated devices in humid atmosphere. Magnetron sputter inert gas aggregation combined with a quadrupole mass filter for cluster size selection was used for single-step Pd nanoparticle deposition in the soft landing regime. Uniformly dispersed, crystalline Pd nanoparticles with size-selected diameters around 5 nm were deposited on single CuO nanowire devices in a four point configuration. During gas sensing experiments in humid synthetic air, significantly enhanced CO response for CuO nanowires decorated with Pd nanoparticles was observed, which validates that magnetron sputter gas aggregation is very well suited for the realization of nanoparticle-functionalized sensors with improved performance.